EDULEXYA: Development of Educational Gamification Application with Interactive Card Media to Improve Learning Outcomes for Children With Dyslexia on The Android Platform - Saputra, Apry Aditya; Jati, Handaru (Journal of Information Engineering and Technology, 2025)
This study addresses the learning challenges faced by children with dyslexia, particularly in writing, spelling, and reading. The objectives are: (1) to analyze user needs and determine suitable application features to support dyslexic children's learning; (2) to design a mobile application, EduLexya, incorporating gamification and interactive card-based multisensory learning methods; and (3) to evaluate the application’s effectiveness in enhancing learning outcomes. Employing a Research and Development (R&D) framework with the Software Development Life Cycle (SDLC) waterfall model, the study involved dyslexic children aged 7–15 years from Somoitan (experimental) and Giriharjo (control) elementary schools. Data collection involved observation, interviews, questionnaires, and pretest-posttest assessments. Statistical analysis included validity, normality, homogeneity, and hypothesis testing via the Independent Samples T-Test. Findings identified essential features—writing, spelling, reading, quizzes, schedules, settings, guides, and feedback. The application was rated highly by material experts (5.00), media experts (4.81), and beta testers (4.81). Posttest results showed a significant improvement in the experimental class (M = 84.37, Sig. 0.000) over the control class (M = 74.33, Sig. 0.043), confirming EduLexya’s effectiveness in improving dyslexic learners’ academic outcomes.